A mendelian randomisation study of the causal effect of exercise intensity on the development of type 2 diabetes - Yu, Fengliang; Bi, Haixiang; Qian, Haonan; Li, Shunji (Frontiers in Physiology, 2024)
Objective: This study examines the causal effects of varying exercise intensities on type 2 diabetes mellitus (T2D) through Mendelian randomization (MR) analysis, using genetic variants as instrumental variables.Methods: A two-sample MR analysis was performed, employing inverse variance weighting (IVW) as the primary method, supported by weighted median, MR-Egger regression, MR-PRESSO, and MR robustness-adjusted contour scores. Data were obtained from the International Exercise Genetics Database (IEGD) and the Global Diabetes Research Consortium (GRC), encompassing over 150,000 individuals for exercise intensity and around 200,000 T2D patients and controls. SNPs linked to exercise intensity were selected based on genome-wide significance (P < 5×10^-8) and linkage disequilibrium criteria (distance >10,000 kb, r^2 < 0.001).The IVW analysis suggested that high-intensity exercise might reduce T2D risk, but the association was not statistically significant